Adoption of improved animal husbandry practices by dairy farmers - JOGAL, K V; TRIVEDI, S M; LAKHLANI, C D (The Indian Journal of Animal Sciences, 2022)
Livestock sectors plays a very important role in Indian economy. It provides sustainable source of income for many marginal and small farmers. However, the dairy livestock owners are yet ignorant with scientific management practices. If feeding, breeding, health care and other management practices fit in proper operation, it would be possible to reach the desired level of milk production. The present study aims to assess the adoption of improved animal husbandry practicies by dairy farmers. Primary data was collected from 120 dairy farmers of Rajkot district. Adoption Index was used to study the adoption of improved animal husbandry practices by farmers. The results reveald that among improved animal husbandry practices, the highest adoption was of health-care management practices followed by clean milk production practices, breeding management practices, feeding management practices. The lowest adoption was found in calf rearing practices. Full adoption was recorded in feeding of dry fodder, feeding of green fodder, cultivation of fodder crops and observation of ailing animals whereas non adoption of animal husbandry practices was observed in dehorning of calves and feeding of silage.